1985
DOI: 10.1104/pp.79.4.1094
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Dependent Channels Found in the Membrane Fraction of Corn Mitochondria

Abstract: Transmembrane channels have been found in the membrane fraction of corn (Zea mays W64AN) mitochondria that exhibit a remarkable resemblance to the voltage dependent anion-selective channels (VDAC) located in the outer membrane of animal (Rattus norvegicus), protist (Paramecium aurelia), and fungal (Neurospora crassa) mitochondria.The channels in corn were demonstrated to be essentially identical to VDAC channels in three characteristic properties: (a) single channel conductance magnitude, (b) weak anion sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 25 publications
3
25
0
Order By: Relevance
“…The channel reopened (downward deflection) as the applied voltage returned toward zero. Thus, as is the case for VDACs from other sources such as R. norvegicus (Colombini, 1979), Z. mays (Smack and Colombini, 1985), or S. cerevisiae (Forte et al, 1987), MmP29 produces a channel that closes at both positive and negative potentials.…”
Section: Measurements Of Channel-forming Activity As Determined From mentioning
confidence: 92%
See 3 more Smart Citations
“…The channel reopened (downward deflection) as the applied voltage returned toward zero. Thus, as is the case for VDACs from other sources such as R. norvegicus (Colombini, 1979), Z. mays (Smack and Colombini, 1985), or S. cerevisiae (Forte et al, 1987), MmP29 produces a channel that closes at both positive and negative potentials.…”
Section: Measurements Of Channel-forming Activity As Determined From mentioning
confidence: 92%
“…Channels with properties essentially indistinguishable from those of VDAC channels from other sources such as Paramecium aurelia (Schein et al, 1976), Neurospora crassa (Freitag et al, 1982), Rattus norvegicus liver (Colombini, 1983), Zea mays root (Smack and Colombini, 1985), or Saccharomyces cerevisiae (Forte et al, 1987) were observed when MmP29 was reconstituted into planar phospholipid membranes. Like other VDAC channels, MmP29 inserted spontaneously when 10 to 20 pL of a Triton X-100-solubilized sample (1% v/v) was added to the aqueous solution (about 4 mL) on one side of the planar membrane.…”
Section: Measurements Of Channel-forming Activity As Determined From mentioning
confidence: 97%
See 2 more Smart Citations
“…Until now, however, the only plant channels studied using this technique were plant mitochondrial "VDAC" channels (28) and a Ca2+ channel from giant-celled algae (9). In this work, thylakoid vesicles were fused into planar lipid bilayers (17), and single channel events were observed.…”
mentioning
confidence: 99%